Analysis Of The Potential For Cbl Inland Waterways As An Alternative Transport Logistics Using AHP. (July 2020) - Wahyu Nur Pradana, Bagas; Thareq Abdul Fattah, Muammar; Didiet Rachmat Hidayat, Raden; Himawan Triyasa, Doddy; Yuliantini,
Abstract: Economic growth in Indonesia gives effect to the development of the logistics industry in Indonesia. Logistics Business is a sector that has a fairly high growth rate, where increasingly improved growth requires effective and efficient logistical support. In 2018, the Government of West Java implement the Innovation Inland Waterways which aims to create a channel width of the sea into the mainland so that containers can be transported by water rather than through the toll-road to Tanjung Priok, and make Inland Waterways as an Alternative Transportation logistics, Central Government, also has made Inland Waterways Cikarang Bekasi Laut (CBL) as the National Strategic Projects, which is expected to reduce the current density on the land logistics from Cikarang Industrial Area to the Port of Tanjung Priok and aim to optimize the potential of the river as an alternative canal path of transport logistics. Where the volume of land transport logistics in Indonesia has reached nearly 90%, and with the construction of CBL Inland Waterways is expected to reduce costs with the integration of multimodal transport logistics. The purpose of this study was to find a potential that can be developed as Alternative Transportation Logistics and determines the priority level of that potential. Retrieval of data taken through a questionnaire distributed to experts in the field of logistics and related to the research being carried out. The result indicated that the Economic aspect was the top priority among the other potential to developed.